Kinetics and Mechanism of the Hydrolysis of Benzylidene Benzoylhyd - Razone Derivatives - Maher Abu-Eid; Foad M. Mahmoud; Bassem F. Shraydeh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The kinetics and mechanism of hydrolysis of a series of substituted benzylidene benzoylhydrazones (X — BBH) have been studied at five different temperatures in the range 25 — 45°c by U. V. -visible spectrophotometry. The hydrolysis reactions were found to follow first - order kinetics. A mechanism has been postulated in which the attack of water on the protonated substrate is subject to general base catalysis. This mechanism has been supported by the effect of anion concentration of buffer, at constant pH, on the observed rate constant. The Bronsted ?-value for the hydrolysis reaction is 0.73. Hammett correlations, Arrhenius and thermodynamic parameters have been evaluated and discussed. The pKa values for the conjugate acids for benzylidene benzoylhydrazones derivatives (X - BBH) have been determined.